2015
DOI: 10.15835/nsb749666
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Three Leafy Vegetables to the Allelopathic Effect of <i>Vitellaria paradoxa</i>

Abstract: This study was conducted to evaluate the growth response of three leafy vegetables (Celosia argentea, Amaranthus cruentus and Amaranthus hypochodriacus) to the leaf extract of Vitellaria paradoxa. Forty-five (45) experimental plastic containers were filled with 5 kg of loamy soil each and randomly allocated to the following regimes: control, 20 g, 40 g, 60 g and 80 g of powdered leaves of V. paradoxa, in three (3) replicates for each test crop respectively. It was observed that the response of the three leafy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This suggest that the effects of the extract are concentration dependent. This affirms the reports of Folarin et al, (2015), Marley et al, (2004), , and Kolawole et al, (2018) who found the effects of some tree species on vegetables and crops to be concentration dependent with significant difference between treatments.…”
Section: Discussionsupporting
confidence: 91%
“…This suggest that the effects of the extract are concentration dependent. This affirms the reports of Folarin et al, (2015), Marley et al, (2004), , and Kolawole et al, (2018) who found the effects of some tree species on vegetables and crops to be concentration dependent with significant difference between treatments.…”
Section: Discussionsupporting
confidence: 91%
“…It is recommended that crops grown under Shea trees are shade tolerant [1]. More so, an increasing number of studies find that Shea tree has inhibitory effects on certain crops [1,10–12]. The magnitude of the inhibition ranges from those that are not statistically significant and do not cause significant differences in yields, to those that are statistically significant leading to significant reduction in yields.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of planting season and crop productivity under Shea has not been widely reported. Majority of the studies on inhibitory effects of Shea tree are single season studies such as those of Aleem et al, 2014, [11] or bioassays that involve planting the experimental crops in soils incorporated with extracts of mature Shea tree components such as those of Folarin et al, 2015, [12]. It is widely accepted that variations in seasons have significant influence on crop productivity [1].…”
Section: Introductionmentioning
confidence: 99%
“…A number of scholars and 40 stakeholders agree that there is need to conserve Vitellaria paradoxa due to its economic 41 potential and threats to it (Buyinza & Okullo, 2015). These threats include burning the tree 42 for charcoal, and large scale clearing of the Shea tree to pave way for mechanized agricultural 43 production ( Folarin et al (2015). It is widely accepted that variations in seasons have significant influence on crop productivity (Boffa, 2015).…”
Section: Introduction 28mentioning
confidence: 99%